An Analysis of Demographics and Attributing events in Sexual Offence cases reported at One stop Centre – A Retrospective study - Moses , TMK; Sravani, Y; Rao , PV; Reddy, NS; Manasa, M; Alekhya , M (Journal of Indian Academy of Forensic Medicine, 2024)
This retrospective study aims to analyze the demographic characteristics and event attributes of sexual assault survivors who sought assistance at One-Stop Center (OSC) in Visakhapatnam, India, between 2021 and 2022. The OSC, known as Sakhi, provides comprehensive medical, legal, and psychological support to women affected by sexual assault. The study collected relevant data from entry register including information on age, literacy, socioeconomic status, residence, relationship to the perpetrator, consent, time of reporting, and the sections under which the cases were registered. A total of 288 cases were analyzed, revealing significant findings regarding the demographics and characteristics of sexual assault survivors. The study found that the majority of survivors were above 25 years old, followed by those between 19 and 24 years old. The cases primarily involved literate individuals from low socio economic background with a higher prevalence of cases in urban areas. Intimate partners were identified as the primary perpetrators in most cases, while force or coercion was reported in 20% of incidents. The study provides valuable insights into the characteristics and patterns of sexual assault cases and emphasizes the need for targeted interventions to prevent sexual assault and support survivors based on their specific needs. These findings contribute to a better understanding of sexual assault dynamics and development of nationwide prevention strategies and support services for survivors.